DOUBLE-STATOR SWITCHED FLUX PERMANENT MAGNET MACHINES HAVING LOW ROTOR POLE NUMBERS (Nigerian Journal of Technology, 2018)
In this paper, double-stator switched flux permanent magnet (DS-SFPM) machines having low rotor numbers and whose stator teeth and rotor pole numbers are relatively same is investigated. Quantitative comparison of their electromagnetic performance is also given. Two-dimensional finite element (2D-FEA) analysis is employed in the prediction of the developed machines’ performance. It is observed that the open circuit flux-linkage waveforms of the analysed machines having odd rotor poles are both symmetrical and sinusoidal in contrast to its even number rotor pole counterparts whose waveforms are asymmetrical, non-sinusoidal and unbalanced. More importantly, the developed machines with odd rotorpole numbers exhibit higher torque density than its even rotor pole equivalents. http://dx.doi.org/10.4314/njt.v37i3.26